2013
DOI: 10.1177/239700221302700303
|View full text |Cite
|
Sign up to set email alerts
|

Work Life Balance up in the Air – Does Gender Make a Difference between Female and Male International Business Travelers?

Abstract: Work life balance up in the air-Does gender make a difference between female and male international business travelers? ** Managing work-life balance (WLB) has become an issue for both employees and HR departments since WLB tensions may reduce performance, overall job satisfaction and finally, increase the fluctuation rate. Having a balance between job and non-work is a particular challenge for international business travelers, but research on this topic is still in its very infancy. The aim of this article an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 81 publications
(185 reference statements)
0
13
2
Order By: Relevance
“…We controlled for gender, children, and age. The selection of these control variables was based on studies revealing that women experience more emotional exhaustion (Purvanova & Muros, 2010) and poorer work-life balance in the context of business travel than men (Kollinger-Santer & Fischlmayr, 2013). Jensen (2014) found that parental responsibility was positively related to work-family conflict among business travelers.…”
Section: Control Variablesmentioning
confidence: 99%
“…We controlled for gender, children, and age. The selection of these control variables was based on studies revealing that women experience more emotional exhaustion (Purvanova & Muros, 2010) and poorer work-life balance in the context of business travel than men (Kollinger-Santer & Fischlmayr, 2013). Jensen (2014) found that parental responsibility was positively related to work-family conflict among business travelers.…”
Section: Control Variablesmentioning
confidence: 99%
“…Employees asserted that to accommodate all employees' work–family needs, HR departments should provide tailored support (Kollinger‐Santer & Fischlmayr, ; Fischlmayr & Kollinger, ). In cases where organisations provided one‐size‐fits‐all support, different unions elicited different outcomes because the support in place did not always solve employees' work–family issues (Ravenswood & Markey, ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies explore work-life issues and work-family conflicts related to gender and global careers (Hearn et al 2008;Hutchings et al 2012;Mäkelä and Suutari 2011). Finally, reflecting changing employment and work patterns, there are recent studies on work-life issues for employees who undertake frequent international business travel (e.g., Hearn et al 2008;Kollinger-Santer and Fischlmayr 2013;Kvande 2009) and particularly for women on international assignments (Shortland 2014). There is also emerging research on employees in developing economies who may be integral to the operations of an MNC; cross-cultural research exploring different national perspectives of work-life offers insights to inform MNC managers about how to approach work-life in local contexts (e.g., Masuda et al 2012).…”
Section: Understanding Work-life Management In the Global Contextmentioning
confidence: 99%
“…Given the investment in expatriates and knowledge workers, it is valuable for researchers to investigate work-life issues for strategically important employees in MNCs, such as expatriates (e.g., Fischlmayr and Kollinger 2010;Lazarova et al 2010;Rosenbusch and Cseh 2012;Shih et al 2010). Recent research examining the impact of changing employment patterns and exploring 'new' or different employment modes in MNCs is also valuable (e.g., Kollinger-Santer and Fischlmayr 2013;Mäkelä and Suutari 2011). It is encouraging that researchers have responded to calls such as those by Agars and French (2011) to move beyond a focus on middle-class, white-collar positions.…”
Section: Hrm System and Work-life Management In Mncsmentioning
confidence: 99%